Improving site selection in clinical studies: a standardised, objective, multistep method and first experience results. Issue 7 (12th July 2017) - Hurtado-Chong, Anahí; Joeris, Alexander; Hess, Denise; Blauth, Michael
Abstract : Introduction: A considerable number of clinical studies experience delays, which result in increased duration and costs. In multicentre studies, patient recruitment is among the leading causes of delays. Poor site selection can result in low recruitment and bad data quality. Site selection is therefore crucial for study quality and completion, but currently no specific guidelines are available. Material and methods: Selection of sites adequate to participate in a prospective multicentre cohort study was performed through an open call using a newly developed objective multistep approach. The method is based on use of a network, definition of objective criteria and a systematic screening process. Illustrative example of the method at work: Out of 266 interested sites, 24 were shortlisted and finally 12 sites were selected to participate in the study. The steps in the process included an open call through a network, use of selection questionnaires tailored to the study, evaluation of responses using objective criteria and scripted telephone interviews. At each step, the number of candidate sites was quickly reduced leaving only the most promising candidates. Recruitment and quality of data went according to expectations in spite of the contracting problems faced with some sites. Conclusion: The results of our first experience with a standardised and objective method of site selection are encouraging. The site selection method described here can serve as a guideline for other researchers performing multicentre studies. Trial registration number: ClinicalTrials.gov: NCT02297581 .